Central Retinal Artery Occlusion and Its Visual Prognosis In An African Population-Analytical Comparative Retrospective Study (Global Journal of Medical Research, 2023)
Introduction Central Retinal Artery Occlusion CRAO is a blinding severe ophthalmic emergency but more serious still is its indirect replica of possible mortality in affected individuals Aim To assess visual prognosis of large series of patients after being diagnosed with CRAO Materials and Methods Records of patients who had been managed for CRAO were reviewed retrospectively for safety complication visual outcome and prognosis Patients demographic data indications of treatment and length of follow up were collected and analysed using Chi square and paired t-tests Results A total of 40 eyes of 40 patients 15 females and 25 males were identified Mean age at diagnosis was 70 4 3 5 range68-75 years with minimum follow up period of 5 years range 5 8 Visual acuities were poor in all eyes 40 100 Ten patients 25 died from various cardiovascular diseases
Keywords: retinal artery occlusion; sudden loss of vision; ocular emergency; eye stroke